A RANDOMIZED TRIAL OF THE NYU CAREGIVER INTERVENTION IN COMMUNITY SETTINGS IN ISRAEL—ISSUES AND OUTCOMES. (11th November 2018) - Mittelman, M; Clay, O; Werner, P
Abstract: The NYU Caregiver Intervention (NYUCI) is a multicomponent intervention which has demonstrated both short and long-term benefits, including reduced depression and stress and improved physical health of the primary family caregiver, thereby enabling them to postpone or avoid nursing home placement of their relatives with dementia and reducing the cost of dementia to the health system. The study of the NYUCI in Israel NYUC (Lituf) is the first randomized controlled trial of the NYUCI completed in a non-English speaking country. The major outcome of interest was caregiver depression, measured with the Geriatric Depression Scale, 15-item version. Among 100 spouse caregivers who enrolled, 81 provided depression data at baseline and at one or more post intervention assessments. A linear random effects regression model, controlling for factors associated with depressive symptoms, was used to compare the trajectories of depressive symptoms in the intervention and the usual care control groups over the 2 year study period. Results revealed that those who received the NYUCI reported a declining number of depressive symptoms, while those in the control group experienced a small increase in number of symptoms, demonstrating that the Israel NYUCI was effective in reducing depressive symptoms reported by spouse caregivers (p <0.05). While jmplementing an evidence-based study in the community posed unique challenges, it was a more real-life trial of the applicability of the NYUCI in Israels. Because of the positive results, 26 municipalities are now implementing the intervention across Israel, delivered by professional counselors on the payroll of the Ministry of Welfare.